Persepsi Kemudahan Aplikasi Bank Jago (Studi Deskriptif pada Pemberi Komentar Instagram @jadijago Kurun Waktu November 2023 – Januari 2024) - Farach Devona; Meria Octavianti; Yuliana Dewi Risanti (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
The COVID-19 pandemic has accelerated the adoption of digital banking services, with one in three people becoming users. This has led to a significant digital transformation and an increase in the number of digital banks. Understanding the perception of ease of use is crucial for technology acceptance. This study aims to understand users' perceptions after using the Bank Jago application and identify which features influence this perception. The Technology Acceptance Model is the foundation of this research. A quantitative method is used by distributing questionnaires via Google Forms to 89 samples, selected through Simple Random Sampling from commenters on @jadijago’s social media posts from November 2023 to January 2024. This research employs a descriptive approach to analyze the data obtained. The data is processed using descriptive statistics to present the frequency, mean, and distribution of users' perceptions of the ease of use of the Bank Jago application. The results indicate that respondents' ratings of Perceived Ease of Use (PEOU) are very high, with 48 respondents (53.93%) rating it in the top category. Among six indicators and 13 questions, the highest average is on the Controllable indicator (4.30) and the lowest on the Easy to Become Skillful indicator (4.03).